Problemy pomiaru skuteczności i efektywności zastosowań controllingu - Nowosielski, Krzysztof (The Problems of Measurement of Controlling Efficiency and Effectiveness, 2006)
In the paper the requirements of controlling effectuations measuring were signaled. The essence and methods of the measurement of controlling efficiency and effectiveness in the enterprise were described. The attention was paid to specific, consultative role of controlling towards management system and influence of this role on application possibilities of different offsets. The basic problems, which can appear in compliance of efficiency and effectiveness of controlling measurement, were also identified in the paper.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1104, s. 351-357